STUDENT PERCEPTION TOWARD USING GEMINI IN EFL CLASSROOM - Salsabil, Salfadila; Rafly Aprian, Mohammad; Tarihoran, Naf'an (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
This study aims to investigate students’ perceptions toward the use of Gemini in the English as a Foreign Language (EFL) classroom, particularly in writing activities. This research employed a descriptive quantitative design involving 20 students from an English Education program, with data collected through a questionnaire based on the Technology Acceptance Model (TAM), focusing on perceived usefulness, perceived ease of use, learning motivation, learner autonomy, and challenges. The findings reveal that students generally have positive perceptions of using Gemini, as it helps them generate ideas, organize their writing, and improve sentence construction. It is relatively easy to use, despite some difficulty understanding its responses. In addition, Gemini shows a stronger impact on learner autonomy than motivation, as it supports independent learning and self-correction. However, concerns related to overreliance and reduced creativity were also identified. Therefore, although Gemini has strong potential to support EFL writing instruction, its use should be properly guided to ensure it functions as a supportive learning tool rather than a replacement for students’ own thinking. Furthermore, 80% of students agreed that Gemini helps generate ideas. At the same time, 70% reported improvement in writing organization.